1978
DOI: 10.1111/j.1365-2559.1978.tb01702.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes in the placenta and decidua after induction of abortion by extra‐amniotic prostaglandin

Abstract: Seventeen placentae from second trimester abortions induced by the injection of extra-amniotic prostaglandin have been examined. The extraplacental membranes, the chorionic plate of the placenta, the placental intervillous space and the placental villi were normal in all cases. In all but one specimen lesions were, however, noted in the decidua, these including focal decidual necrosis, intradecidual haemorrhage, thrombosis of maternal vessels and dilatation and congestion of the maternal vasculature. Similar d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…4 What was completely unexpected, and unprecedented, was the observation of highly PP13 enriched ZONEs within the decidua. Several observers of gestational endometrium have previously noted decidual necrosis, 28,29 but they did not decipher an organized pattern. They also assumed that the necrosis represented either a pathologic process associated with pregnancy loss, or when seen in elective terminations of normal pregnancies, they did not attribute it to a specific physiologic role in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…4 What was completely unexpected, and unprecedented, was the observation of highly PP13 enriched ZONEs within the decidua. Several observers of gestational endometrium have previously noted decidual necrosis, 28,29 but they did not decipher an organized pattern. They also assumed that the necrosis represented either a pathologic process associated with pregnancy loss, or when seen in elective terminations of normal pregnancies, they did not attribute it to a specific physiologic role in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of locally adminis tered prostaglandins. Fox et al [7] were un able to differentiate treated from control cases by decidual histology, because there were nonspecific lesions present in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…The placenta has been evaluated in many studies on patients with habitual abortion and some pathological conditions have been thought to cause abortion. 11 Apoptosis is seen more frequently in the placenta of patients with habitual abortion than in that of patients with spontaneous abortion. 12 In addition, it has been shown that perivillous fibrin deposition, chronic villitis, chronic histiocytic intervillositis, and plasma cell deciduitis are higher in chromosomally normal habitual abortions than in spontaneous abortions.…”
Section: Introductionmentioning
confidence: 99%
“…The placenta has been evaluated in many studies on patients with habitual abortion and some pathological conditions have been thought to cause abortion. 11 …”
Section: Introductionmentioning
confidence: 99%